Gq-Coupled Receptors in Autoimmunity. (17th January 2016) - Zhang, Lu; Shi, Guixiu
Abstract : Heterotrimeric G proteins can be divided into Gi, Gs, Gq/11, and G12/13 subfamilies according to their α subunits. The main function of G proteins is transducing signals from G protein coupled receptors (GPCRs), a family of seven transmembrane receptors. In recent years, studies have demonstrated that GPCRs interact with Gq, a member of the Gq/11 subfamily of G proteins. This interaction facilitates the vital role of this family of proteins in immune regulation and autoimmunity, particularly for G α q, which is considered the functional α subunit of Gq protein. Therefore, understanding the mechanisms through which Gq-coupled receptors control autoreactive lymphocytes is critical and may provide insights into the treatment of autoimmune disorders. In this review, we summarize recent advances in studies of the role of Gq-coupled receptors in autoimmunity, with a focus on their pathologic role and downstream signaling.